Działalność usługowa Banku Spółdzielczego w Podegrodziu - Żelasko, Renata (My University, 2015)
Banki spółdzielcze są najstarszą formą spółdzielczości na terenie Polski. Powstały one na bazie kas pożyczkowo-oszczędnościowych. Do chwili obecnej wiele z banków w tym także Bank Spółdzielczy w Podegrodziu cieszy się 150 letnim zaufaniem wśród swoich odbiorców jak również stażem istnienia swojej działalności. Celem niniejszej pracy jest prezentacja wszystkich dostępnych usług w Banku Spółdzielczym w Podegrodziu. Zaczynając od usług podstawowych (otwarcie rachunków bankowych, lokat i zobowiązań kredytowych) a kończąc na usługach pomocniczych (otrzymanie kart bankowych, ubezpieczeń pomieszczeń gospodarczych). Analiza badawcza została przeprowadzona za lata 2012-2014. Dzięki materiałom otrzymanym od Banku Spółdzielczego w Podegrodziu udało się przeprowadzić analizę poszczególnych usług bankowych wraz z ich wysokością. Ponadto w pracy tej zbadano sytuację finansową banku wykorzystując w tym celu analizę wskaźnikową. Na podstawie tych dwóch analiz udało się sformować wnioski dotyczące działalności usługowej BS w Podegrodziu.

Co-operative banks are the oldest form of the cooperative movement in Poland. They came into existence on the basis of loan-and-saving cash desks. By now many of banks including the co-operative bank in Podegrodziu are pleased 150 with lukewarm confidence amongst one’s recipients as well as with the intership of the existence of one’s activity. A presentation of all available services is a purpose of this work at the co-operative bank in Podegrodziu. Starting with basic services (opening banking accounts, deposits and credit obligations) and finishing on ancillary services (receiving bank cards, of insurance of utility rooms). Research analysis was conducted in years 2012-2014.Thanks to materials received from the co-operative bank in Podegrodziu managed to conduct analysis of individual banking facilities along with their height. Moreover at this work a financial standing of the bank was examined using the ratio analysis to the destination. Based on these two analysis managed to form applying applications of BS service activity into Podegrodziu.
Service activity of the co-operative bank in Podegrodziu
Keywords: bank spółdzielczy; odbiorca; usługa bankowa; system bankowy; cooperative bank; recipient; banking service; banking system; analiza badawcza; research analysis